Effects of Phosphorus Fertilizer, Poultry Manure Applications with Bacillus megaterium M-3 Inoculation on Yield and Yield Components of Common Vetch (Vicia sativa) - Kaynar, Dilara; Çomaklı, Binali (Journal of Agricultural Production, 2024)
Phosphorus is considered one of the essential elements for legumes as it increases nitrogen fixation due to nodulation. Hence, for high productivity in legumes, it should be added as inorganic or organic fertilizer to soils containing insufficient phosphorus. Especially in recent years, using inorganic and organic fertilizers together has gained importance in terms of sustainable agriculture, considering plant growth and soil and environmental health together. The effects of three different doses of phosphorus fertilizer (0, 50, 100 kg P2O5 ha-1), and two different doses of poultry manure (0, 3 t ha-1) applications with two different doses (B0 or B1) of phosphorus solubilizing bacteria (Bacillus megaterium M-3) inoculation on hay yield and yield components of common vetch were examined in this study. In fact, while the highest hay yield and crude protein rate were obtained by bacterial inoculation together with phosphorus fertilizer application, the effect of poultry manure application on yield and yield parameters was variable. Instead, the applications had no significant effect on the number of main branches, ADF and NDF rates. Consequently, the application of 100 kg P2O5 ha-1 together with Bacillus megaterium inoculation can be recommended for high hay yield in common vetch under irrigated conditions in areas with poor or medium soils in terms of phosphorus.
Keywords: Field Crops and Pasture Production (Other); Fertilizer; Hay yield; Phosphorus; Phosphorus-solubilizing bacteria; Tarla Bitkileri Yetiştirme ve Islahı (Diğer)